Análise da relação entre a estratégia e os sistemas de controle gerencial: um estudo com empresas do setor da construção civil - Danilo Lacerda Borges (2013)
This research was carried out to analyze the known interactions between the strategic business formation and management control systems used by them, these have been formal, rudimentary or even not formally structured, having as analyzes parameter the levers of control recommended by Simons (1995). In this way, it was performed a multiple case study in two construction civil companies situated in metropolitan region of Belo Horizonte/MG. From this perspective it was found that those companies use the generic strategy of focus to sell their enterprise, with this strategy one organization has long-term planning while the other do not have a strategy, guiding by perspectives and perceptions of short-term. As for management control system, it is noted that due to ISO 9001 and PBQP-H certifications these companies have several control tools focused on control quality, such as vision, mission, procedures manuals and quality manuals. However it was noted that some of these tools exist in order to meet established standards and audits by certifications institutions, it is not being used, in some situations, in the day to days organization and neither as a tool to make a decision. Accordingly, it was concluded that the relationship between managerial controls and strategy formation of these organizations occurs passively, serving the management control system as guarantors of strategy achievements and organizational goals, but it not being used effectively as a way of identifying opportunities and source of forming new strategies. However it was noted with the organizations employees the importance of these systems come to be used more actively in strategy formation, it being understood that for such use being made becomes necessary a better structuring of the managements control systems of these companies and a consequent better utilization of them. It was suggested for future researches a deeply management control systems of construction companies and their strategies.